An assessment of oral health status, tobacco use and cancer awareness among tea plantation workers (Irula tribes), Nilgiri Hills, Tamilnadu, India - Delfin Lovelina Francis (Tobacco Induced Diseases, 2018)
Background Tea is an important agro-industry of India, which contributes immensely to the countries economy. Tea garden population constitutes approximately 1/12th of tea growing state´s population. Poor socio-economic conditions, ignorance due to illiteracy, over-crowded and unhygienic living conditions in the residential colonies make tea garden population vulnerable to various communicable diseases and malnutrition. Hence this study was contemplated with an aim to assess the oral health status, tobacco use and cancer awareness among tea plantation workers, Nilgiri Hills, Tamil Nadu, India.